HOLINESS AND SOCIETY - Shoval, Ronen. Link ([S.l.])
1 online resource
Keywords: Exploring the subtle political philosophy within the Biblical narrative, this book presents enduring insights that complement Ancient Greek philosophy for contemporary political distinctions - uncovering overlooked socio-political ideologies to provide a unique perspective alongside the classical philosophical tradition. By adopting a sociological approach, Ronen Shovel interprets the Bible as a reflection of perspectives and ideologies, emphasizing the intricate dynamics between rulers and subjects, balancing justice, and power within societies. A key focus is the examination of holiness as a distinct political category, influencing institutions, ethics, justice, and even the use of force. This perspective challenges traditional religious scholarship, merging sociology with the concept of holiness. Holiness and Society enriches political philosophy, religious studies, and sociology, broadening their boundaries and offering fresh perspectives, serving as a bridge between antiquity and modernity, providing valuable insights into contemporary political thought.